Measuring multiple-source based academic writing self-efficacy - Bråten, Ivar; Haverkamp, Ymkje E.; Latini, Natalia; Strømsø, Helge I. (Frontiers in Psychology, 2023)
Although writing self-efficacy has been a productive line of research for several decades, no prior writing self-efficacy measure has focused on students' self-efficacy for integrating information across multiple sources when producing an academic text. To fill this gap in existing research on the measurement of writing motivation, we designed a measure targeting the extent to which students are confident that they can write an academic text that integrates content from several different sources. In a study with Norwegian undergraduate students (n = 136), this measure, which we called the the Multiple-Source based Academic Self-Efficacy Scale (MAWSES), was validated by means of confirmatory factor analysis and relationships between the resulting unitary construct and other relevant constructs. The findings provided evidence concerning the reliability and validity of the MAWSES. In future research, this measure could be included as an independent variable to predict processes and products of multiple-source based, integrated academic writing, as a moderator or mediator of effects in writing intervention research, or as an outcome variable in its own right.